Urgent decision-making in extreme circumstances: Associations with cognitive reflection and with responses to moral dilemmas - Cosentino,Alejandro César (2020)
It has been proposed that urgent decision making in extreme circumstances may be based on two systems of information processing: affective and rational (Cosentino, Azzollini, Depaula, & Castillo, 2017). Given that the model of urgent decisions has been recently developed, the aim of this study was to determine its characteristics and relationships with relevant variables: (a) the tendency to inhibit dominant but incorrect responses and to promote a reflective process that leads to the correct responses and (b) the resolution and difficulty of high-conflict personal moral dilemmas. We used an intentional sample of 416 university students from a military academy. The results showed that urgent decision making in extreme circumstances is related to general preferences for intuition or deliberation, cognitive reflection, and reaction to high-conflict personal moral dilemmas. Notably, urgent decision making based on rationality was positively associated with cognitive reflection and a utilitarian way of solving high-conflict personal moral dilemmas. Also, both rational and affective/emotional urgent decision-making types were found to be associated with the perceived difficulty in solving the dilemmas. The model of urgent judgments in extreme circumstances can be useful because it contributes to describing the optimal cognitive and decisional profile for the selection of human resources in activities that involve facing contexts of high uncertainty where fast decision making is required, such as tasks performed by professional rescue or combat personnel.